ASPECTS OF MODERN DIAGNOSIS AND TREATMENT OF LIVER ABSCESS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Liver abscess is defined as a pus-filled formation in the liver that can develop as a result of liver damage or intraabdominal infection disseminated from the portal circulation. Purpose of the study: improvement of modern methods in the diagnosis and treatment of liver abscess. Material and methods. In the Khorezm regional Multidisciplinary Medical Center, 75 patients treated with "liver abscess" diagnosis were retrospectively and prospectively analyzed in the period from 2015 to 2021. The patients were divided into two groups. Results. The negative effect on the patient's body was not detected when using the FarGA1LS solution. According to the results of a bacteriological examination, no bacterial growth was observed in both groups in liquids that came out of the residual cavity. Conclusion: With an abscess of adipose tissue caused by the action of antiseptics of FarGALS and chlohexidine solutions, the bacteriological effect is not observed, therefore, this antiseptic does not have a bactericidal effect on adipose tissue.